2015
DOI: 10.1038/ncomms7722
|View full text |Cite
|
Sign up to set email alerts
|

Autoprocessing of neutrophil elastase near its active site reduces the efficiency of natural and synthetic elastase inhibitors

Abstract: An imbalance between neutrophil-derived proteases and extracellular inhibitors is widely regarded as an important pathogenic mechanism for lung injury. Despite intense efforts over the last three decades, attempts to develop small-molecule inhibitors for neutrophil elastase have failed in the clinic. Here we discover an intrinsic self-cleaving property of mouse neutrophil elastase that interferes with the action of elastase inhibitors. We show that conversion of the single-chain (sc) into a two-chain (tc) neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…In combination, this suggests that impaired cytokine secretion by professional APCs is not a contributing factor in CH25H‐deficient mice. Furthermore, recent evidence revealed that depletion of alveolar macrophages ameliorated elastase‐induced emphysema (Ueno et al , ), an iBALT‐independent emphysema mouse model (Dau et al , ; Sarker et al , ). Therefore, we utilized this model to demonstrate that loss of CH25H in macrophages did not impact upon emphysema development.…”
Section: Resultsmentioning
confidence: 99%
“…In combination, this suggests that impaired cytokine secretion by professional APCs is not a contributing factor in CH25H‐deficient mice. Furthermore, recent evidence revealed that depletion of alveolar macrophages ameliorated elastase‐induced emphysema (Ueno et al , ), an iBALT‐independent emphysema mouse model (Dau et al , ; Sarker et al , ). Therefore, we utilized this model to demonstrate that loss of CH25H in macrophages did not impact upon emphysema development.…”
Section: Resultsmentioning
confidence: 99%
“…Other escape mechanisms exist, including an intrinsic self‐cleaving process near the S1 pocket that was described for murine HNE. This effect transforms single‐chain into two‐chain HNE and reduced the inhibitory effects of α1‐AT and synthetic small molecules .…”
Section: Nsps Actions Within and Outside The Neutrophil And Interactimentioning
confidence: 99%
“…To produce a catalytically inactive variant of NE, we mutated the Ser195 to Ala195 by inserting an oligo duplex (DJ3532 (5′-GTGAACGTATGCACTCTGGTGCCACGTCGGCAGGCAGGCATCTGCTTCGGGGACGCT-3′) and DJ3533 (5′-CGTCCCCGAAGCAGATGCCTGCCTGCCGACGTGGCACCAGAGTGCATACGTTCACAC-3′)) into the Alf I site of the previously described wildtype mouse NE construct in pTT5 (Dau et al . 26 . To enable site-specific labeling of NE, we added a C-terminal short peptide with a cysteine flanked by three aspartate residues on each side by the insertion of an oligoduplex (DJ3632 (5′- CTAGCGACGACGATTG CGACGATG ATC-3′) and DJ3633 (5′- CTAGGATCATCGTCGCAATCGTCGTCG-3′)) into the Avr II site.…”
Section: Methodsmentioning
confidence: 99%